Bullying Prevention Through Gestalt Approach Using Group Setting In Increasing Self-Control - Firman; Zikry Latupasjana Ersya; Yeni Karneli (Bisma The Journal of Counseling, 2022)
This study aims to determine the effectiveness of implementing the Gestalt Setting Group counseling approach to improve self-control in preventing student bullying. The population of this study were students of SMKN 1 Padang. The sample in this study was the students of SMK N 1 chosen by random cluster sampling. This type of research was experimental with a Quasy-Experiment control group design. The instrument used is a self-control questionnaire in bullying prevention using a Likert scale. Data were analyzed using the Wilcoxon Signed Ranks Test and SPSS version 21.00. The results showed that in the experimental group before being given the Gestalt setting counseling approach, the average pretest score of the group was 138.6, and after being given the Gestalt setting counseling approach the group's average posttest score increased to 187.33. However, in the control group, the pretest score was 134.4, and after being given the Gestalt setting counseling approach to the group, the group's average posttest score increased to 136.4. It can be concluded that "there is a significant difference in student self-control between the experimental and control groups"